Preliminary Study of a Prismatic-Core Advanced High-Temperature Reactor Fuel Using Homogenization Double-Heterogeneous Method. (1st February 2020) - Alrwashdeh, Mohammad; Alameri, Saeed A.; Alkaabi, Ahmed K.
Abstract: The double heterogeneity of the tristructural isotropic (TRISO) fuel in the prismatic-core advanced high-temperature reactor should be accurately and correctly modeled and analyzed, especially for a large-scale loaded with the double-heterogeneity effect. The reactivity-equivalent physical transformation method was developed and employed to enable homogenizing TRISO fuel in a high temperature reactor considering the double heterogeneity and taking into account the large problem involved in performing the whole-core burnup calculation using Monte Carlo transport codes with double-heterogeneity problems. In this work, the heterogeneous effects of a collision of probability calculation method were used to represent the effects of scattering anisotropy on the leakage rates and the isotropic streaming effects due to low optical density in the model. The WIMS and DRAGON codes have been used to perform the calculations of double heterogeneity for the TRISO fuel, fuel compact, and fuel element and the results are compared with the SERPENT Monte Carlo code.